Experience in the Use and Evaluation of the Therapeutic Efficacy of a Drug Based on Para-Aminobenzoic Acid in the Complex Therapy of Herpesvirus Conjunctivitis and Keratitis - N. G. Zumbulidze; V. M. Khokkanen; I. B. Litvin (Oftalʹmologiâ, 2023)
According to statistics, infectious and inflammatory eye diseases of various etiologies are widespread in the world (about 18 million cases per year). In some cases, they are severe and can lead to a decrease in acuity and even loss of vision. About 12 million in the structure of infectious and inflammatory diseases of the eye are conjunctivitis, which may be accompanied by inflammation of the edges of the eyelids (blepharoconjunctivitis) and / or the cornea (keratoconjunctivitis). A viral infection is one of the common causes of inflammation of the mucous membrane of the eyes. In the routine practice of ophthalmologists, adeno- and herpesvirus lesions of the organ of vision are most often diagnosed. Eye diseases of herpetic etiology are among the most common infections. Herpetic conjunctivitis usually develops as a result of an initial attack by Herpes simplex virus type 1 (HSV-1) in early childhood. But there is reason to believe that in adults they are no less common than herpetic keratitis, however, the diagnosis of isolated herpetic conjunctivitis is extremely rare, since, unlike herpetic keratitis or creatoconjunctivitis, the clinic is less pronounced, not always confirmed by laboratory, which leads to underdiagnosis. During the treatment of ophthalmic herpes, one should rely not only on the antiviral effect of drugs, but also on the presence of immunomodulators (interferons or inducers of endogenous interferonogenesis) in the complex therapy, which contribute to faster recovery with fewer relapses.The aim of this study was to evaluate the effectiveness of the use of the drug OCTALMOL in the treatment of 34 patients with conjunctivitis and keratitis of herpesvirus etiology. The drug contributed to the relief of clinical symptoms of inflammation and a reduction in the duration of therapy in 89 % of patients, while the average duration of treatment was 10.7 ± 0.3 days. The therapeutic effect in the group where OCTALMOL was included in the basic therapy was statistically higher than in the control group.